The Comparison Test BCBT an Reduction on SDS and BCS - Purnomo, Indra Dwi; Ismail, Rosnah; Suharsono, M (Jurnal Psikologi Perseptual, 2025)
The provision of drug treatment within overcrowded prisons presents significant challenges. This study investigated the effectiveness of Brief Cognitive Behavioral Therapy (BCBT) in reducing methamphetamine dependence severity and craving intensity among incarcerated individuals. A quantitative experimental design compared an intervention group to a control group. Following the screening of 551 prisoners, 170 participants meeting inclusion criteria were randomly assigned to either the BCBT (n=85) or control (n=85) condition. The BCBT group received four individual therapy sessions with two follow-ups over six months. The control group received standard psychoeducational leaflets. The Severity Dependent Scale and a brief craving scale were administered pre- and post-intervention to assess changes in methamphetamine dependence and craving levels. Results indicated a statistically significant decrease in craving within the BCBT group, whereas craving tended to increase in the control group. These findings align with the understanding that recovery is multifaceted, influenced by addiction severity, recovery engagement, and social support, including self-awareness. In conclusion, BCBT demonstrates efficacy in reducing methamphetamine dependence and craving among incarcerated people who use drugs.